2007
DOI: 10.2353/ajpath.2007.060456
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin-α4β1 Integrin Interactions Regulate Metalloproteinase-9 Expression in Steatotic Liver Ischemia and Reperfusion Injury

Abstract: Ischemia/reperfusion injury is a major cause of the highly dysfunctional rate observed in marginal steatotic orthotopic liver transplantation. In this study, we document that the interactions between fibronectin, a key extracellular matrix protein, and its integrin receptor ␣4␤1, expressed on leukocytes, specifically up-regulated the expression and activation of metalloproteinase-9 (MMP-9, gelatinase B) in a wellestablished steatotic rat liver model of ex vivo ice-cold ischemia followed by isotransplantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 55 publications
(57 reference statements)
6
68
0
Order By: Relevance
“…Additionally, matrix proteases facilitate the movement of leukocytes along the vasculature. Matrix metalloproteinase (MMP)-9, a gelatinase family member, is highly expressed after IRI (97). Its blockade results in impaired myeloperoxidase activation and decreased leukocyte accumulation (98).…”
Section: Ho Systemmentioning
confidence: 99%
“…Additionally, matrix proteases facilitate the movement of leukocytes along the vasculature. Matrix metalloproteinase (MMP)-9, a gelatinase family member, is highly expressed after IRI (97). Its blockade results in impaired myeloperoxidase activation and decreased leukocyte accumulation (98).…”
Section: Ho Systemmentioning
confidence: 99%
“…We have recently demonstrated that MMP-9 is expressed by leukocytes in damaged livers (33) and that MMP-9-specific inhibition impairs leukocyte migration in liver I/R injury (29). To evaluate whether COX-2 deficiency was linked to MMP-9 regulation in liver I/R injury, we performed zymography analyzes using SDS-PAGE/gelatin gels to access enzymatic activity in the liver specimens.…”
Section: Mmp-9 Expression Was Reduced In Cox-2-deficient Livers Aftermentioning
confidence: 99%
“…First-strand synthesis and PCR were performed as previously described (33). Transcripts were amplified with Platinum TaqDNA polymerase SuperMix (Invitrogen) on Gene Amp PCR system (Applied Biosystems).…”
Section: Rt-pcr and Quantitative Pcrmentioning
confidence: 99%
“…Similarly to iNOS, MMP-9 is virtually absent in naive livers, and it is highly up-regulated in damaged livers after I/R injury. 15,19,23 In this study, we use iNOS deficient mice and mice treated with a specific iNOS inhibitor to test the hypothesis that iNOS expression has a regulatory function on MMP-9 activation in liver I/R injury. We demonstrate that specific iNOS inhibition markedly down-regulates MMP-9 activity, disrupts leukocyte migration, and reduces apoptosis in liver I/R injury.…”
mentioning
confidence: 99%
“…15,16 Matrix metalloproteinase (MMP)-9 is one of two major gelatinases in the MMP family responsible for the turnover and degradation of several ECM proteins, including fibronectin, 17 a key ECM protein expressed very early by liver endothelial cells in response to injury, 18 including to I/R injury. 19 The expression of MMP-9 has been linked to numerous pathological conditions, such as tumor invasion, 20 inflammation, 17 arthritis, 21 cerebral I/R injury 22 liver I/R injury, 15,23 and liver transplantation. 24 In general, MMPs have a large propeptide containing cysteine, a catalytic domain with zinc at the active center, and a hemopexin-like domain.…”
mentioning
confidence: 99%